Effects of Malnutrition on Neutrophil/Mononuclear Cell Apoptotic Functions in Children with Acute Lymphoblastic Leukemia - (:unkn) unknown (Routledge, 2017)
Background: Recent studies claim that apoptosis may explain immune dysfunction observed in malnutrition. Objective: The objective of this study was to determine the effect of malnutrition on apoptotic functions of phagocytic cells in acute lymphoblastic leukemia (ALL). Materials and Methods: Twenty-eight ALL patients (13 with malnutrition) and thirty controls were enrolled. Neutrophil and mononuclear cell apoptosis of ALL patients and the control group were studied on admission before chemotherapy and repeated at a minimum of three months after induction of chemotherapy or when the nutritional status of leukemic children improved. Results: The apoptotic functions of both ALL groups on admission were significantly lower than those of the control group. The apoptotic functions were lower in ALL patients with malnutrition than those in ALL patients without malnutrition, but this was not statistically significant. The repeated apoptotic functions of both ALL groups were increased to similar values with the control group. This increase was found to be statistically significant. Conclusions: The apoptotic functions in ALL patients were not found to be affected by malnutrition. However, after dietary intervention, increased apoptotic functions in both ALL patient groups deserve mentioning. Dietary intervention should always be recommended as malnutrition or cachexia leads to multiple complications. Enhanced apoptosis might originate also from remission state of cancer. © 2017 Taylor & Francis Group, LLC.